Determination of Composition and Palatability of Certain Weeds - Atanas Kirilov; Natalia Georgieva; Ina Stoycheva (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2016)
The aim of this study was to determine the chemical composition and palatability of certain commonly found weeds (Amaranthus retroflexus, Sorghum halepense, Cichorium intybus, Convolvulus arvensis and Lamium purpureum) in fodder crop areas. As a comparative characteristic of weeds was used alfalfa. Palatability is one of the indicators of fodder quality and it is related to the feed consumption and nutritional value. It was determined through so-called method "cafeteria of manger". The results showed that C. arvensis and A. retroflexus had higher protein content and lower fi ber content of the hay compared to the other weeds with the highest palatability among weeds was C. arvensis (33.89%). This value was close to the palatability of alfalfa hay (38.89%). The second place was occupied by A. retroflexus (16.52%). The remaining weeds (S. halepense, C. intybus, L. purpureum) had considerably lower palatability. The method "cafeteria of manger" is easy to be performed and provides another opportunity to compare different forages.